Direct and Indirect Speech Acts of Apologizing in â€œVenom Let There Be Carnageâ€ Movie - Bagus Wahyu Utomo; Zia Hisni Mubarak (Institut Agama Islam Negeri Palopo, 2023)
The objective of this research is to identify direct and indirect apologizing speech acts in the utterances of the characters in the movie